Nondestructive Localization of Surface Particles for Elemental Compositional Analysis by TOF-SIMS - Lee, Wah-Pheng; Koh, Song-Foo; Yow, Ho-Kwang; Tou, Teck-Yong (2005)
A surface particle localization system based on oblique angle dark field optical scattering has been incorporated into time-of-flight secondary ion mass spectrometry. (TOF-SIMS) In this design, oblique incident laser light would be scattered to all directions by surface particles on silicon wafer and be collected at oblique angle to determine the x-y coordinate of the particle detected. This fast and nondestructive technique is an effective alternative to the standard method for imaging and localization of surface particles using primary ion bombardment by TOF-SIMS which might result in the alteration or loss of physiochemical information from the surface particles. (C) 2005 The Electrochemical Society.